Federal Civil Rights Litigation Pursuant to 42 U.S.C. §1983 as a Correlate of Police Crime - Stinson, Philip Matthew Sr. (Criminal justice policy review, 2019)
The Civil Rights Act of 1871 (codified at 42 U.S.C. §1983 and commonly referred to as Section 1983) provides a civil remedy for aggrieved persons to sue state actors who under the color of law violate federally protected rights. Since the 1960s, there has been an explosion of Section 1983 litigation in the federal courts against police officers and their employing municipal and county agencies. Due to a lack of official statistics and poor methodologies, research has yet to determine how common Section 1983 actions are against the police nationwide. This study examines the relationship between police crime and being named as a party defendant in a federal court Section 1983 civil action. Using a list of 5,545 nonfederal sworn law enforcement officers who were arrested for committing one or more crimes during the years 2005 to 2011, searches were conducted in the federal courts’ Public Access to Courts Electronic Records (PACER) system to locate Section 1983 actions against those officers. The authors found that 22% of all arrested officers were named as a party defendant in a Section 1983 federal court civil action at some point during their law enforcement careers. Additional findings address various predictors of a police officer being sued in a Section 1983 action.